Introduzione alle lingue storiche minoritarie del nord Italia - Erica Autelli; Marco Caria; Riccardo Imperiale (Linguistik Online, 2024)
Italy shows a multitude of languages and dialects bound to different areas, language communities, ethnicities and personal identities. Many of the historical minority languages of Italy are not known to everyone, not even to all Italians though living on the same territory. This special issue aims at describing such language varieties to be found in the Northern pat of Italy, dealing first of all with the history of a certain language variety. Each paper also describes the main linguistic charactericics, mainly at phonological, semantical and morphosyntactic level. Then some of the most important intiatives to preserve such valuable inheritage.